Des pratiques d’artistes et de chercheuses en écologie sonore - Piché, Claire (Recherches féministes, 2009)
This article is an incursion into the domain of sound ecology based on interdisciplinary research about artists and researchers. We expose the fundamental principles of sound ecology, a discipline that emerged during the seventies, and discuss the best practices of women in sound ecology, demonstrating how this constitutes a relevant research area for women’s studies. The link between feminism and sound ecology being established, we summarize three sociopolitically relevant research projects whose methods resemble feminist action research. We conclude by reflecting on the best means to foster interdisciplinary collaboration.
Publisher: Revue Recherches féministes

Au delà du sexe et de la technologie : les tendances du genre - Piché, Claire (eContact!, 2006)